NORTHERN EUROPE AND THE LOOMING RUSSIA: IS EUROPE (NOT) ENOUGH? Different approaches to a European integrated defence: the cases of Norway and Finland. - Bertoldini, Raul (Univerzita Karlova, Fakulta sociálních věd, 2023)
RAUL BERTOLDINI MASTER'S THESIS ABSTRACT 08/2023 NORTHERN EUROPE AND THE LOOMING RUSSIA: IS EUROPE (NOT) ENOUGH? Different approaches to a European integrated defence: the cases of Norway and Finland This master's thesis investigates Finland and Norway's geopolitical landscape and security strategies amid Europe's evolving security environment. The research scrutinises how these Nordic nations have managed their relations with the European Union (EU), North Atlantic Treaty Organization (NATO), and Russia, set against the backdrop of the Russian invasion of Ukraine and escalating tensions in the Arctic region. An in-depth analysis of historical contexts, paths to EU membership, and debates on NATO affiliation underscore the intricate balance these countries maintain in preserving their unique national identities and sovereignty while engaging with regional structures and alliances for security. The study illustrates how the Ukraine conflict prompted strategic realignments, with both Finland and Norway opting for closer ties with the EU and NATO to protect their sovereignty, yet they perceive the security guarantees offered by these two organisations differently. Ultimately, the thesis offers valuable insights into the adaptive and proactive strategies these countries employ in response to current. RAUL BERTOLDINI MASTER'S THESIS ABSTRAKT 08/2023 NORTHERN EUROPE AND THE LOOMING RUSSIA: IS EUROPE (NOT) ENOUGH? Different approaches to a European integrated defence: the cases of Norway and Finland Tato diplomová práce se věnuje analýze geopolitického prostředí a bezpečnostních strategií Finska a Norska v kontextu měnícího se bezpečnostního prostředí Evropy. Výzkum zkoumá vztah těchto severských zemí vůči Evropské unii (EU), Severoatlantické alianci (NATO) a Rusku, a to na pozadí ruské invaze na Ukrajinu a eskalujícího napětí v Arktickém regionu. Důkladná analýza historických souvislostí, cesty ke členství v EU a debat o připojení k NATO poukazuje na komplikovanou rovnováhu, kterou tyto země udržují při zachovávání ...